Bimbingan Teknis Pemanfaatan Jerami Padi Sebagai Pakan Ternak Sapi Potong di Kecamatan Ladongi Kabupaten Kolaka Timur - Musram Abadi; La Ode Nafiu; La Ode Arsad Sani; Hamdan Has; Yaman Yaddi; Putu Nara Kusuma Prasanjaya (Jurnal Pengabdian Masyarakat Ilmu Terapan, 2023)
Rice straw is the main waste that is usually stored and used by farmers as animal feed during the long dry season when fresh forage is difficult to obtain. Various treatment methods have been used to increase the nutritional value of rice straw. One of them is fermentation technology that can increase the nutrition of rice straw. This community service activity aims to increase the knowledge of the farming community, breeders through technical guidance in developing the ability to use rice straw as dry season animal feed in the Ladongi sub-district, East Kolaka Regency. The method used is lecture, discussion, demonstration, and practice. The targets of this activity are farmers in general and groups of farmers at the location of the activity. The results of this community service activity are that farmers are very interested and motivated to use straw as an alternative feed for cattle. The target is to understand and understand rice straw processing technology, namely the manufacture of straw ammonia which is more practical and easier than other straw processing technologies